SiΛvio: a trigger for Λ-hyperons - Münzer, Robert Helmut; Berger, Martin; Fabbietti, Laura; Averbeck, R.; Andronic, A.; Barret, V.; Basrak, Z.; Bastid, N.; Benabderrahmane, Mohamed Lotfi; Buehler, P.; Cargnelli, M.; Čaplar, R.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
As online trigger for events containing Λ hyperons in p+p collisions at 3.1GeV a silicon-based device has been designed and built. This system has been integrated close to the target region within the FOPI spectrometer at GSI and was also employed as a tracking device to improve the vertex reconstruction of secondary decays. The design of the detector components, read-out, the trigger capability as well as the tracking performance are presented. An enrichment factor of about 14 was achieved for events containing a Λ-hyperon candidate.
Gesehen am 07.09.2020
Im Titel ist [lamda] als griechischer Buchstabe dargestellt